Economic geography a contemporary introduction - Coe, Neil M.; Yeung, Henry Wai-Chung; Kelly, Philip F. 1970- (Wiley-Blackwell, 2020)
"Economic Geography is an engaging and accessible introduction to the different ways modern economic geographers understand, analyze, and interpret economic processes. This comprehensive text addresses significant questions relevant to contemporary economic life, from the activities of transnational corporations to issues surrounding workplaces and consumption. It encourages readers to explore how spatial patterns, places, networks, and territories shape large-scale economic processes. Accessible, highly-illustrated material presents fresh insights from the field--complemented by relatable, real-world examples that help students understand the social, cultural, and political contexts underpinning global economic processes. Now in its third edition, this extensively revised and updated textbook retains the features and thematic structure that have proved popular with students and instructors alike, while adding exciting new content. New chapters explore how the global economy and global development are institutionalized and governed, the economic geographies of global climate change, economic practices outside the capitalist mainstream, the role of migrants in labour markets, global production networks, and more"--